The Balloon Tree - Phoebe Gilman (Scholastic Canada Ltd. Hong Kong, 1984)
Before he went away, Princess Leora's father told her to release a bunch of balloons if anything went wrong. Now her grumpy uncle wants to be king and the first thing he does is pop every balloon in the kingdom.
Keywords: Read Aloud -- Read Aloud